Tracing the non-traditional journey of selected community college presidents - Cross, Joyce A., author; Davies, Timothy Gray, advisor (Colorado State University. Libraries, 2002)
Historically the traditional pathway to the community college presidency has been through the academic ranks. According to recent studies, only a little over four percent of all current public community college presidents come to the position from pathways outside of higher education. The purpose of this study was to explore the non-traditional pathway and experiences that brought six leaders to the community college presidency between 1990 and 2001; to analyze the skills and experiences these presidents drew upon from their non-traditional journey to lead their respective community colleges; and, the challenges, disappointments and rewards they encountered since assuming a community college presidency. A phenomenological approach provided a level of depth and substance necessary to understand their particular journey as a distinctive process. Six participants representing approximately 20 percent of the total non-traditional community college presidency were identified for the study and represented prior career categories of Business/Industry; Government/Political; Public Schools; and Governmental Education. Qualitative methods for gathering and analyzing data were used. Along with in-depth interviews with each participant in their respective offices, additional interviews were conducted with governing board trustees, employees, and colleagues of the participating presidents. In addition, the researcher's observational journal notes, presidential position announcements, newspaper articles, and speeches by the participants rounded out the data gathering. Findings revealed common traits among the six participants included: 1) strong, proven leadership skills; 2) persuasive interpersonal skills; 3) positive political relationships and influences; and, 4) a passion and appreciation for education, particularly the community college and its mission. Challenges and disappointments expressed by the participants included a lack of adequate resources; productivity and priorities; decision-making processes; bureaucracy and politics; and adjustments to change. Common rewards cited by the presidents included the ability to share in the successes and make a difference in the lives of students. These presidents who followed a non-traditional pathway did draw from their past experiences particularly in the areas of public relations and interpersonal skills; political relationships; and business orientations. Yet, the non-traditional participants in this study did not reveal unique qualities, attributes, challenges, disappointments or rewards different from those documented in the literature related to their traditional presidential colleagues.
Keywords: school administration; higher education; educational administration